IMPLEMENTASI DAN ANALISA KINERJA SISTEM UJI PADA RANCANGAN ALAT UJI PENETRASI STANDAR SNI 1811-2007 - Eril Kapri; Boy Rollastin; Muhammad Yunus (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Requirements so that the product can be declared passed and standardized. One of the tests carried out is penetration testing, this test is carried out to determine the mechanical properties of the material being tested. In this research, a test instrument is made for penetration testing, where in this test it can be known directly, what happens to the material being tested when a sharp object is punctured or an impact with a sharp object occurs. The penetration tester identifier is made in the form of a cylinder with a PVC guide pipe with a size of 1 inches. To determine the accuracy of the test equipment, the indenter is dropped on the test material from a certain height, namely 160 cm, for the data collection process by marking the indentation marks and visually observing them. For the indenter material used 4340 aisi steel because the steel can be hardened to a hardness of 50 HRC. In the penetration test equipment there are forces acting. The force is that the indenter has a gravity of 30.9 joules. And the potential energy when the identor falls from a height of 1.6 m is 49.44 joules. And the velocity of the identor when it falls is 5.6 m/s.